Impact on T-cell depletion and CD34+ cell recovery using humanised CD52 monoclonal antibody (CAMPATH-1H) in BM and PSBC collections; comparison with CAMPATH-1M and CAMPATH-1G. - Williams, R; Clarke, E; Blair, A; Evely, R; Hale, G; Waldmann, H; Brookes, S; Pamphilon, D (2000)
BACKGROUND: Ex vivo T-cell depletion of allogeneic BM (BM) grafts can effectively reduce graft versus host disease (GvHD) and may also apply to transplantation of allogeneic peripheral blood stem cell (PBSC) transplants. METHODS: Here we have evaluated T-cell depletion and progenitor cell recovery by antibody-mediated cells lysis using three CD52 monoclonal antibodies (MAbs) at different concentrations and cell densities. RESULTS: CAMPATH-1M was superior to CAMPATH-1H for T-cell depletion of BM samples. Treatment with CAMPATH-1M resulted in up to 2.55 log depletion of CD3+ cells, with recoveries of >or=45% CD34+ cells, >or=67% CFU-GM and >or=65% BFU-E. CAMPATH-1H treatment resulted in up to 1.64 log depletion of CD3+ cells and similar recoveries of CD34+ cells, CFU-GM and BFU-E as seen with CAMPATH-1M. Depletion of CD19+ cells was similar to that observed for CD3+ cells while natural killer (NK) cells were relatively spared compared with the T and B cell populations. Log depletions of T cells from PBSC, as determined by immunofluorescence studies and limiting dilution analyses, were similar using CAMPATH-1M, -1H, and -1G. There were also no differences in the depletion of CD19+ cells or NK cells using the three MAbs. Similar results were obtained for recoveries of CD34+ cells, CFU-GM and BFU-E using all three MAbs, although the recovery of CD34+ cells using the highest concentration of MAbs was significantly greater in CAMPATH-1H treated samples. Increasing the number of PBSC treated with CAMPATH-1H and -1M had no effect on the log depletion of T, B or NK cells and there were no major differences in the log depletions achieved with CAMPATH-1H or -1M. Likewise, the higher PBSC density had no effect on the recoveries of CD34+ cells or committed progenitors and once again CAMPATH-1H gave similar recoveries to those obtained using CAMPATH-1M. DISCUSSION: Although CAMPATH-1M resulted in greater ex vivo T-cell depletion of BM than CAMPATH-1H, in all other respects, the humanised CAMPATH-1H was just as effective as CAMPATH-1M and -1G.